Cost control-zero base budgeting and cost drivers - Borthwick, John Alistair Stewart (My University, 2016)
No abstract
A research report submitted to the faculty of commerce of the University of the Witwatersrand in part completion of the degree of Master of commerce, by coursework
Keywords: Cost control--Case studies; Zero-base budgeting--South Africa--Case studies; Overhead costs--Case studies